Análise experimental da fadiga mecânica em argamassas colantes. - Alencar, Douglas Rogério Leite (2020)
Material commonly used in buildings, adhesive mortars are present on facades, walls and floors, composing a coating system that, due to its situation of direct contact with the environment, is under tensions that may vary with time. The study hereby performed and presented in this document, is the experimental study of adhesive mortars previously classified as A, B, C and D. These mortars were classified according to consistency, open time, slip, adhesion resistance, compression resistance, static tensile strength in flexion, static and dynamic elasticity modules and fatigue in flexion tensile. For this, 180 prismatic and 12 cylindrical specimens were molded. The fatigue failure studies were carried out through a tensile test in flexion with a fixed frequency of 10 Hz, using the stress ratios 0.9, 0.8, 0.7 and 0.6 of the static rupture stress. The number of cycles until their ruptures were recorded and used to obtain S-N graphs for each material. The results showed that the studied material presents a high coefficient of variation the closer the actuation loads are to the breaking limits, fatigue life between 104 and 105 cycles, absence of fatigue resistance limit in the range of relative stresses used. Mortar B presented the greatest uncertainty and the lowest number of average cycles and Mortar C presented the best result in this regard. Regarding the elasticity modules, mortars with smaller modules showed higher numbers of fatigue cycles. After the characterization tests carried out on the 4 types of adhesive mortars, the mortars could be classified as ACI for mortars A, B and C and ACII for D, according to NBR NBR 14081-1 to 5.